Integrated Cost Accounting and Investment Analysis: Transformative Insights for Strategic Decision-Making and Financial Performance Enhancement - Kamal, Cut Nadira Putri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
In navigating the complex and dynamic landscape of contemporary business, there is an increasing demand for innovative strategies in decision-making, resource allocation, and sustainable growth. Integrated Cost Accounting and Investment Analysis (ICAIA) has emerged as a revolutionary framework, offering a comprehensive method that intertwines the principles of cost accounting and investment analysis. This extensive study employs a mixed-methods approach, utilizing in-depth interviews, case studies, and a large-scale survey to thoroughly examine the effectiveness of ICAIA implementation. The qualitative data analysis, facilitated by NVivo 12 software, uncovers a positive correlation between the adoption of ICAIA and enhanced financial performance. This improvement manifests in higher profit margins, increased return on assets, and a larger market share for organizations implementing ICAIA. The perceived benefits by these organizations span a spectrum, including augmented decision-making precision, strategic alignment, cost efficiency, and improved competitive positioning. The success of implementing ICAIA is contingent on several factors, prominently featuring robust leadership commitment, seamless data integration, and a culture emphasizing continuous improvement. This study presents compelling evidence that ICAIA not only offers a transformative paradigm for strategic decision-making but also contributes significantly to the enhancement of financial performance. Organizations that embrace ICAIA and cultivate a data-driven culture are poised for long-term success in the ever-evolving business landscape.